Chloride diffusivity in saturated cement paste subjected to external mechanical loadings. (1st February 2015) - Du, Xiuli; Jin, Liu; Zhang, Renbo
Abstract: The chloride diffusivity in cement-based composite materials is mainly affected by the multi-scale pores, including gel pores, capillary pores, entrained and entrapped voids, etc. The pore-structure parameters, e.g. pore size, pore connectivity, pore surface roughness and pore volume fraction (porosity), will be changed under external mechanical loadings. And this leads to the change of the chloride diffusivity in cement paste. The porosity is regarded as the primary parameter of water-saturated cement paste, and the effect of the external mechanical loadings on the chloride diffusivity in cement paste is treated as the change of porosity on the chloride diffusivity. Saturated cement paste is regarded as a two-phase composite composed of intrinsic cement matrix and pore-water inclusion. A two-phase spherical model is developed, and the quantitative relationship between current porosity of cement paste and initial porosity as well as volumetric strain is evaluated based on the theory of elasticity. Moreover, a theoretical formula for the simulation of chloride diffusivity in cement paste is obtained. Finally, the effects of external mechanical loadings (herein i.e. the volumetric strain) and porosity variation on the chloride diffusion behavior of cement paste are explored based on the Fick's second law. It is found that chloride diffusion coefficient of saturated cement paste increases greatly with the increase of initial porosity. Furthermore, the diffusion coefficient decreases with the increase of compressive volumetric strain, and increases with the increase of the tensile volumetric strain. Highlights: A theoretical method is developed for predicting chloride diffusivity in cement paste under external mechanical loadings. The porosity of cement paste will change under external loadings, causing the change of chloride diffusivity. The apparent chloride diffusion coefficient of cement paste is closely related to volumetric strain and initial porosity.